Relationship Between Mental Health and the Education Level in Elderly People: Mediation of Leisure Attitude - Belo, Pedro; Navarro-Pardo, Esperanza; Pocinho, Ricardo; Carrana, Pedro; Margarido, Cristovao (Frontiers in Psychology, 2020)
Purpose: The present study intends to explore the influence of education on the mental health of retired people and the mediating role of leisure attitude on this relation. Design/methodology: The sample was simply random, and a confidentiality agreement was established. The sample was composed by 403 Portuguese participants (37.2% male; 62.8% female). The participants completed the MHI and the LAS. Findings: The hypothesized mediation model showed that leisure attitude mediated the association between education and well-being. In addition, highest levels of distress were found in participants with highest level of education. Value: Our results suggest that old-aged people with high education and more positive leisure attitude have a better psychological adjustment concerning well-being. Also, high level of education can lead to a better perception of aging changes (physical, life, profession).